2021
DOI: 10.3390/ijms22083959
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and Male Fertility

Abstract: Over the past decade, telomeres have attracted increasing attention due to the role they play in human fertility. However, conflicting results have been reported on the possible association between sperm telomere length (STL) and leukocyte telomere length (LTL) and the quality of the sperm parameters. The aim of this study was to run a comprehensive study to investigate the role of STL and LTL in male spermatogenesis and infertility. Moreover, the association between the sperm parameters and 11 candidate singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…However, some scholars have suggested that telomere length shortening may be a sign of sperm damage rather than a cause of sperm alteration ( 23 ). In contrast, some studies have concluded that STL is unrelated to sperm parameters ( 24 ).…”
Section: Introductionmentioning
confidence: 94%
“…However, some scholars have suggested that telomere length shortening may be a sign of sperm damage rather than a cause of sperm alteration ( 23 ). In contrast, some studies have concluded that STL is unrelated to sperm parameters ( 24 ).…”
Section: Introductionmentioning
confidence: 94%
“…The estimate of the per-allele effect on TL (base pair increase/decrease according to each allele) for each SNP was obtained from the literature using GWAS data performed using leukocyte TL as outcome of interest [16]. Not all the genotyped individuals reached a call rate of 100%, and for this reason, and to be able to compute comparable score values for all study subjects, we also considered average values for the score (using the teloscore value divided by the number of genotyped SNPs) an approach that was successfully used in other studies [27, 28, 40]. Finally, the teloscore was transformed into quintiles based on its distribution in the controls.…”
Section: Methodsmentioning
confidence: 99%
“…TL is genetically determined, and 11 single nucleotide polymorphisms (SNPs) have shown a strong influence on this trait [16,[24][25][26]. A polygenic score generated with those 11 SNPs, called "teloscore" [15,27], has been successfully used in susceptibility studies of several human traits [28,29], including cancer [16,27,[30][31][32][33][34][35]. The advantage of using a genetic score is that it bypasses all the possible confounders, and it could give a more precise estimation of the causative association between TL and cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, studies in infertile men have shown that patients with short telomeres are unable or less likely to produce good-quality embryos compared to those with longer telomeres [23,33,38]. On the other hand, however, other authors have found no statistically significant differences in reproductive outcomes between spermatozoa with long and short telomeres and donor samples [39][40][41]. Although epidemiological retrospective studies can provide insight into general trends regarding the association between telomeres and infertility factors, they have limitations; these can include the sample size not always being sufficient to validate statistical results.…”
Section: Germ Cell Telomere and Environmental Pollutantsmentioning
confidence: 99%